Pemberdayaan Masyarakat Peduli Lingkungan Melalui Teknologi Pengolahan Minyak Jelantah Menjadi Lilin Wangi - Maulidah, Rifaatul; Sulistyaningsih, Dwi; Sujarwanto, Eko; Sumantri, Agus (Sahira Publishing, 2024)
The Pawindan Village Community, Ciamis District, has become aware of the importance of preserving the environment. It can be seen from the programs initiated by the Kampung Keluarga Berencana Magot and the Usaha Peningkatan Pendapatan Keluarga Sejahtera Flamboyan, such as the